2020
DOI: 10.1371/journal.pone.0229141
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in lignin content and increase in the antioxidant capacity of corn and sugarcane silages treated with an enzymatic complex produced by white rot fungus

Abstract: The objective was to evaluate the effect of the addition of 0, 10, 20, and 30 mg.kg-1 of natural matter of a lignocellulosic enzymatic complex produced by the white rot fungus on the chemical composition, cumulative gas production in vitro, and antioxidant compounds of corn and sugarcane silages. After being chopped and treated with the enzymatic complex, the plants were packed in vacuum-sealed bags. After 60 days, the mini silos were opened and the samples were dried in a forced ventilation oven at 55˚C for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
1
2
1
Order By: Relevance
“…An increase in S/G ratio indicates a reduction in the guaiacyl content and therefore we speculate that laccase in combination with GO can degrade the more condensed guaiacyl linkages as compared to laccase with ABTS. An increase in S/G values with a reduction in lignin has also been reported in literature (Chanoca et al 2019 ; Machado et al 2020 ).…”
Section: Resultssupporting
confidence: 77%
“…An increase in S/G ratio indicates a reduction in the guaiacyl content and therefore we speculate that laccase in combination with GO can degrade the more condensed guaiacyl linkages as compared to laccase with ABTS. An increase in S/G values with a reduction in lignin has also been reported in literature (Chanoca et al 2019 ; Machado et al 2020 ).…”
Section: Resultssupporting
confidence: 77%
“…The higher FA concentration in ETC175-inoculated silages can be beneficial, as a previous report indicated an improvement in meat quality by the addition of 30 mg. kg −1 of FA to the diet of steers [13]. Interestingly, no correlation could be detected between FA concentration, TPC, and DPPH results in our experimental silages in contrast to previous reports on corn silages treated with fibrolytic enzymes [78] or alfalfa silages treated with FAE+ LAB [14]; however, in many cases, different types of determinations and different extraction methods were performed. It is proposed that FA reacts with increasing scavenging activity, but this could not be detected in the present experiment [14].…”
Section: Maize Mini Silo Experimentscontrasting
confidence: 97%
“…It is proposed that FA reacts with increasing scavenging activity, but this could not be detected in the present experiment [14]. The TPC analyzed in this work was generally lower than that previously reported for corn silages [78], which, in that case, correlated with the amount of fibrolytic enzymes applied. The TPC content was negatively correlated with the digestibility measures by Taboada et al [79], as observed in the CRL1446-inoculated group, but not in the rest of the experimental groups of this work.…”
Section: Maize Mini Silo Experimentscontrasting
confidence: 89%
“…The low variation is additional evidence that the ensiling process was efficient and that the ensiled material kept the quality of the fresh forage. Machado et al (2020) discuss how, during the process of cell wall digestion by microorganisms in the rumen, lignin plays a significant role as a constraining element. This is primarily attributed to its strong connection with cellulose and, more notably, with hemicellulose.…”
Section: Resultsmentioning
confidence: 99%